2017
DOI: 10.1002/2016jc012263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mesoscale eddies on Kuroshio intrusion variability northeast of Taiwan

Abstract: Abundant mesoscale eddies propagate to the east of Taiwan and affect the Kuroshio Current and its onshore intrusion northeast of Taiwan. But the dynamical process of how eddy activities modulate the Kuroshio intrusion is still unclear. In this study, in situ ocean velocity observations, drifter trajectories, tide gauge measurements, satellite sea surface height data, and assimilative Hybrid Coordinate Ocean Model (HYCOM) reanalysis outputs were used to analyze a cyclonic eddy‐induced large Kuroshio onshore int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
(73 reference statements)
4
31
0
Order By: Relevance
“…Oey et al () concluded that winter cooling alone could cause a great northward intrusion of KBC onto the ECS shelf. It was reported that the Kuroshio intrusion can be partly attributed to vortex stretching of the intruded water column over topography (Yang et al, ) and to the westward impingement of eddies from the open ocean on the Kuroshio mainstream (Wu et al, ; Yin et al, ). The vertical structure of the Kuroshio intrusion was also inferred from the paths of major currents north of Taiwan (Yang et al, ); as shown in their Figure 14, the Kuroshio turns cyclonically from the surface to the bottom when it intrudes onto the ECS shelf (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oey et al () concluded that winter cooling alone could cause a great northward intrusion of KBC onto the ECS shelf. It was reported that the Kuroshio intrusion can be partly attributed to vortex stretching of the intruded water column over topography (Yang et al, ) and to the westward impingement of eddies from the open ocean on the Kuroshio mainstream (Wu et al, ; Yin et al, ). The vertical structure of the Kuroshio intrusion was also inferred from the paths of major currents north of Taiwan (Yang et al, ); as shown in their Figure 14, the Kuroshio turns cyclonically from the surface to the bottom when it intrudes onto the ECS shelf (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We established another numerical experiment, hereafter designated the M2K case, to investigate the M 2 internal tide variability modulated by the Kuroshio to the northeast of Taiwan. Generally, the Kuroshio intrusion in this area was thought to be a quasi‐steady process with dominant current and transport variability occurring at 100‐day timescales (Johns et al, ; Yin et al, ; Zhang et al, ), which is much longer than the timescale of internal tides. Therefore, the Kuroshio flows and the associated stratification structure could be regarded as a steady background field during the 10‐day period of the ideal tidal experiment (M2T case).…”
Section: Methodsmentioning
confidence: 99%
“…Yin et al . [] showed a good agreement between the HYCOM reanalysis data and AVISO geostrophic currents, and drifter trajectories from Global Drifter Program northeastern of Taiwan (see their Figures and ). Both onshore (positive) and offshore (negative) transports are found.…”
Section: Statistical Analysis Of Oceanic Response To Typhoon Eventsmentioning
confidence: 99%